2013
DOI: 10.1177/1077546312475150
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent damage identification method for large structures based on strain modal parameters

Abstract: Early damage detection not only improves the safety and reliability of structures but also reduces maintenance cost. However, damage detection is difficult to implement in large structures under ambient excitation because of the limitation of sensors, the uncertainty of ambient excitation, and the global properties of modal frequencies and displacement modes. This paper proposes a new damage detection method that employs the real encoding multi-swarm particle swarm optimization algorithm and fitness functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Hong et al [22] conducted a comprehensive comparison of macrostrain mode and displacement mode obtained from distributed macrostrain sensing and high-density point sensing (e.g., accelerometers) technologies. Because of the highly sensitive characteristic to local defects, modal curvature and/or modal strain based quantities have been widely utilized to identify the presence, locations, and severity of damage in dynamic structures by the comparisons of before and after damage [23][24][25][26]. For the assessment of structural status, modal macrostrain vectors, macrostrain frequency response functions, and modal curvatures were successfully applied in structural health monitoring [27,28].…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…Hong et al [22] conducted a comprehensive comparison of macrostrain mode and displacement mode obtained from distributed macrostrain sensing and high-density point sensing (e.g., accelerometers) technologies. Because of the highly sensitive characteristic to local defects, modal curvature and/or modal strain based quantities have been widely utilized to identify the presence, locations, and severity of damage in dynamic structures by the comparisons of before and after damage [23][24][25][26]. For the assessment of structural status, modal macrostrain vectors, macrostrain frequency response functions, and modal curvatures were successfully applied in structural health monitoring [27,28].…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…The intense vibration induced by flood discharge may cause significant damage to hydraulic structures, especially to the accessory structures (e.g., guide walls [1,2], sluice gates [3] and gate piers [4]) on the dam body. Moreover, it had been found that the vibration can be transmitted from the superstructure to the dam foundation, and then to the neighboring ground, which may seriously impact the safety of the nearby buildings as well as the physical and mental health of the building residents.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to fluctuating pressure and vibrational characteristics, conventional research techniques include theoretical derivation [16], model tests [13], prototype tests [17], and numerical simulation [18]. There have also been various damage diagnosis algorithms presented for the guide wall [19,20]. The above studies are focused on structural optimizations and excitations; however, for the vibration mechanism and dynamic response of the guide wall, conventional research methods are inadequate.…”
Section: Introductionmentioning
confidence: 99%